Techniques in doing the question type “rearrange the words or phrases to make a complete sentence” in IOE for grade 5 students: a case study in yen hoa primary school, hanoi = kĩ thuật làm dạng bài “sắp xếp các từ hoặc cụm từ thành câu hoàn chỉnh” trong bài thi IOE dành cho học sinh lớp 5: nghiên cứu tình huống ở Trường tiểu học Yên Hòa, Hà Nội - Phạm, Ngọc Tuyết (2020)
English has been one of the dominant languages all over the world. The need of studying English at the very young age has been put an emphasis on. Therefore, the Ministry of Education and Training has made a decision to organized English competition on the Internet – IOE, which intends to raise the awareness and interest of teaching and learning English. In this study about techniques of doing the “what’s the order?” question type, the researcher would like to conduct a case study relating to a grade 5 student who earned the forth prize of this year district round. By the means of observation and interview mainly, findings about the techniques that the grade 5 student employed, the difficulties he may have and the surrounding environment affects when he did IOE’s “what’s the order?” question type. Capital letters and punctuation marks are the most often used as they make a spine of a sentence. Also the repetition of the same questions makes the student react faster to them. Mostly, the student did not face any big problem when doing the type of question. Family orientation, self discipline and classroom competitiveness made up a motivation for the child to do as best as he can with the “what’s the order?” part and in IOE in general. It is inevitable that the research seems biased since it is just a single case, not the majority. Therefore, it would be better if any other researchers can extend the scale of the study so that it has the validity.